A note on Bazilevič functions - S. A. Halim; D. K. Thomas (International Journal of Mathematics and Mathematical Sciences)
For α>0, let B1(α) be the class of normalized analytic functions defined in the open unit disc D satisfying Re(f(z)/z)α−1f′(z)>0 for z∈D. The sharp lower bound for Re(f(z)/z)α is obtained and the result is generalized to some iterated integral operators.